CANVA PLATFORM: VISUAL CONTENT FOR DEVELOPING WRITING SKILLS OF PROSPECTIVE ENGINEERS IN ESP CLASSES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
This article explores the integration of visual content technologies, with a specific focus on the Canva.com platform, to enhance the teaching of English for specific purposes (ESP) to prospective engineers. The primary goal of the authors was to investigate the effectiveness and benefits of using Canva.com for developing writing skills among prospective engineers through a mix of theoretical research and practical implementation in an educational setting. For this purpose, they implemented targeted activities via Canva.com, provided classroom observations, conducted a literature review, and administered a questionnaire survey with 50 engineering students, which helped to analyze students' work and demonstrate the impact Canva had on the development of students' writing abilities. Canva’s user-friendly interface and visually appealing templates support the mastery of writing, covering various formats like resumes, cover letters, essays, and engineering blueprints. The article not only highlights the potential of Canva.com but goes further to present concrete examples of activities tailored for prospective engineers. Models of both individual visual storytelling and collaborative endeavours, exemplified by the “Evolution of Railway Technology” project, showcase the platform’s versatility in facilitating engaging and educational experiences. In addition to these activities, the authors provide insightful assessment criteria and teaching tips, offering valuable guidance on effectively incorporating Canva.com into the classroom. By seamlessly integrating visuals into writing activities, the authors emphasize the transformative impact on prospective engineers, encouraging them to express ideas more effectively and imaginatively. The Canva.com platform emerges as a dynamic and indispensable tool in ESP classes, cultivating an environment that not only stimulates creativity but also provides structured templates that empower students to navigate the intricacies of writing with confidence. Consequently, the article advocates wholeheartedly for the effective integration of Canva.com in English language instruction for prospective engineers, presenting a compelling avenue to elevate both their writing skills and overall language proficiency.